Uji Sensori Kopi Arabika Pasaman Dengan Menggunakan Metode Seduhan Pour Over V60 (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Tomi Candra, 2024. "Sensory Quality of coffee using the Pour Over V60 Brewing Method". Final project. D4 Hospitality Management Study Program, Department of Tourism. Faculty of Tourism and Hospitality and Padang State University. This research purpose is to analyze the coffee quality using the pour over v60 brewing method in terms of Flavor, Aftertaste, Acidity and Body. As well as knowing the coffee sensory quality using the V60 pour over brewing method and providing information to the public and baristas about the coffee sensory quality using the V60 pour over brewing method. And what is the quality of Pasaman Arabica coffee using the V60 pour over method? This research type include in experiment by making comparisons. The comparison was carried out with 2 comparison aspects and 2 research subjects per comparison aspect, namely grind size and ratio between coffee and water. This research was conducted in the tourism department's barista laboratory on December 1-December 20 2023. The panelists in this research consisted of 3 panelists consisting of 1 tourism department lecturer and 2 expert baristas. Based on the experimental results and after being subjected to organoleptic tests, it was stated that the organoleptic test results after describing the sensory quality of coffee using the pour over v60 brewing method in terms of good flavour, very good aftertaste, quite good acidity and good body.